Analysis of NIS Plasma Membrane Interactors Discloses Key Regulation by a SRC/RAC1/PAK1/PIP5K/EZRIN Pathway with Potential Implications for Radioiodine Re-Sensitization Therapy in Thyroid Cancer - Faria, Márcia (2022)
This article belongs to the Special Issue Role of Small GTPase Signaling in Tumorigenesis